Uji Praktikalitas Pengembangan Media Pembelajaran Informatika Menggunakan Aplikasi Articulate Storyline.3 Kelas X di SMK Dhuafa Padang - Afrilia Syafitri; Indra Wijaya; Popi Radyuli (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This research and development is motivated by the problem of limited Informatics learning media at SMK Dhuafa Padang in the 2022/2023 academic year. This happens because there is no learning media that attracts students' interest in learning. Therefore the author seeks to design interesting learning media for students. This study aims to determine the Validity, Practicality and Effectiveness of Making Learning Media Applications in Class X Informatics Subject at SMK Dhuafa Padang Ta 2022/2023. This study uses research development methods (research & development). The research subjects were 40 people. The research model used is the development research model (ADDIE model), with the design development steps as follows. (1) Analyze, (2) design, (3) development, (4) Implementation and (5) Evaluate. The results of the validity test by the experts as a whole the validator test assessment of Learning Media Applications in Class X Infomartics Subject at SMK Dhuafa Padang is 85.40%, so that the validity level can be interpreted as valid to use. The results of the practicality test assessment as a whole the practicality assessment of the Application of Learning Media in Informatics Class X Subject at SMK Dhuafa Padang is 92.65%, so that the level of practicality can be interpreted as very practical to use. The results of the overall effectiveness test assessment of the effectiveness of the Learning Media Application in the Eye Informatics Class X at SMK Dhuafa Padang is 92.70% so that the level of effectiveness can be interpreted to be very effective. In conclusion, based on the assessment along with expert input as well as the results of field trials of the Learning Media Application as a learning medium, it has been tested for feasibility, superiority, and can be used in the learning process in class X Informatics at SMK Dhuafa Padang.